Development of Sharia Crowdfunding to Support Social Initiatives in the Medan City Muhammadiyah Student Association - Wahyuni, Sri; Marliyah, Marliyah; Siregar, Saparuddin; Fauzi, Muhammad (JESI (Jurnal Ekonomi Syariah Indonesia), 2024)
This research aims to investigate the potential and obstacles to implementing Sharia crowdfunding in supporting the social initiatives of the Medan City Muhammadiyah Student Association. The research method used is a qualitative approach with case studies, involving interviews with administrators and analysis of documents related to previous social initiatives. The research results highlight several main challenges, including limited financial resources, uncertainty in fundraising, and a lack of understanding regarding sharia crowdfunding. With an in-depth analysis of financial challenges, effective communication strategies, and the role of education, this research provides a comprehensive understanding and a concrete foundation for the development of a Sharia crowdfunding model that is appropriate to the organizational context. The implications of these findings include strategic steps to ensure the sustainability and success of social initiatives in the future.